A bibliometric analysis of trends in solar cooling technology. (15th March 2020) - Saikia, Kangkana; Vallès, Manel; Fabregat, Alexandre; Saez, Raúl; Boer, Dieter
Graphical abstract: Highlights: Scientific literature on solar cooling technologies from Web of Science Database. Analysis of statistical trends for countries, authors, journals, and institutions. Collaboration between authors, institutions, and countries is visualized. Co-occurrence network of most frequent keywords to identify hot topics of research. The evolution of various solar cooling technologies is discussed. Abstract: With the increasing demand for air-conditioning and refrigeration and depleting fossil fuel resources, countries across the globe have been exploring sustainable alternatives to supply cooling loads. While solar cooling technology has been investigated and demonstrated in recent decades, it has not yet been able to take over traditional cooling systems due to the technical and financial constraints. Understanding the state of the art in this emerging research field is crucial in planning future research efforts. In light of this motivation, this study uses bibliometric analysis to identify hot topics, trends, and research clusters in solar cooling. A dataset of 3639 publications on solar cooling obtained from Web of Science has been analyzed using (i) the open source tool VOSviewer, (ii) the R package Bibliometrix and (iii) an in-house bibliometric tool. This analysis allowed us to determine the annual publication rate both total and segregated by country, author, journal, and research institution. With an overall increasing trend in the total number of publications, China was identified as the leading country in solar cooling research followed by the USA, and Southern European countries. Keyword analysis and time evolution of various key solar cooling technologies have shown that the focus has so far been on solar thermal cooling technology. Nonetheless, as solar photovoltaic prices drop significantly, researchers are expected to focus more closely on photovoltaic driven cooling systems in the near future as a step towards reducing fossil fuel dependence and mitigating climate change.